Shaft - Tidyman, Ernest (Great Britaine Corgi Books, 1972)
Publisher description: Mention Shaft, and most people think of Richard Roundtree in a long, black leather overcoat, purposefully striding down crowded New York streets to an infectiously funky soundtrack. But a full year before Gordon Park's seminal 1971 movie--which turned the unknown Roundtree into a star and featured Oscar-winning music by Isaac Hayes--New York private eye John Shaft was already strutting his stuff in Ernest Tidyman's original novel. Following Shaft's attempt to track down the daughter of Harlem crime boss Big Daddy, Tidyman's plot is thick with Chandler-esque double-dealing and his dialogue alert to the rhythms of street culture. As Shaft prepares to hit our screens once more--this time Samuel L. Jackson steps into the role for John Singleton's big-budget remake--it's a good time to revisit the private eye's roots, and check out the novel which started it all ... Can you dig it?
Keywords: Tidyman, Ernest -- Organized crime